UNJUK KERJA SISTEM PROTEKSI ARUS LEBIH GARDU INDUK 150 KV SEI. RAYA PONTIANAK - Harry Furqan . (Faculty of Engineering, Universitas Tanjungpura, 2015)
ABSTRACT In the last two years (from January 2013 to December 2014), at the main substation 150 kV Sei.Raya, 4.373 cases of CB were opened due to disruption of various types. There were 1.829 times where it was indicated that it was trip in the Ground fault and 675 times where the trip happened due to Phase fault, potentially causing outages, damage to equipment and to the system. Due to this, it is necessary to perform research on the performance of the relay overcurrent protection system at 150 kV substation Sei.Raya. Based on the calculations from secondary data obtained from PT.PLN (Persero) Area Pengatur Distribusi and Penyaluran (APDP) Kalimantan Barat by using help from the MATLAB program for the calculation of the interference in the short-circuit current from the smallest bus 18 to bus 17 that is equal to 1436,281 amps. Where the calculation is used to obtain the short-circuited current value that is read on the device and to determine the working time where the current relay has passed the value of 1436,281 amps. The results that were obtained from this research show that Ihs > Iset that is (8,9768> 1,75), which means the relay is working. For the TMS (time multiplier setting) values of 0.15 (field data) then setting the relay time to 0.5seconds while in the calculated working time for interference 1 Ø – landing on bus 17 at 0.63 seconds and on bus 18 at 0.87 seconds. Key words: TMS, PSM, Overcurrent relay, Ground fault, Phase fault.